INTERNET MAPPING - MUSTAPHA KAMAL, AHMAD FAIZ (Universiti Teknologi Petronas, 2004)
Geographical Information System (GIS) are methods to visualize, manipulate, analyze, and display spatial data. GIS application software such as Arc View or Maplnfo allows the integration of such GIS maps with programming language software such as Visual Basic. As we all know, internet has been a major information distribution channel. If we could integrate both GIS map and serves it in a web browser medium, we could provide GIS applications online, the users could manipulate and handle each map with their own choice. In order to create the Internet map that allows GIS map, Arc IMS will be use. ArcIMS runs in a distributed environment and consists of both client and server components. The ArcIMS HTML Viewer and ArcIMS Java Viewers are client-side components. The ArcIMS Spatial Server, ArcIMS Application Server, ArcIMS Application Server Connectors, and ArcIMS Manager are server-side components. As a conclusion, Internet mapping benefits the user by clearly indication GIS data to them.